The effectiveness of advertising campaign of diabetes among children / Nur Salihah Omar - Omar, Nur Salihah (Faculty of Art and Design, 2013)
Diabetes is a condition where there is excess sugar in the bloodstream. This occurs because the body lacks a hormone called insulin is needed to convert sugar into energy for our bodies. Insulin is a hormone that is produced by an organ called the pancreas that are in the stomach. Kite body produce energy to carry out daily tasks of food consumed daily. In the stomach, food and sugary starchy foods called carbohydrates converted into a substance called sugar or glucose and enters the blood stream where it will be used by the body to produce energy.For chapter 1, this section was including the background for this research. It stated the statement of problems, limitation and literature review about the research. This section also explains the reason of the research and the benefits that arrived. Based on the literature review, further explanations made from the sources and references that related to area of this research.Type 1 diabetes is the most common form of the disease among children in the present age. It is caused by the inability of the pancreas to produce insulin. The cause of this disease is unknown but it is believed that the environmental factors, genetic and dietary factors also. It gives the impression to the girls and boys.